2017
DOI: 10.1021/acs.orglett.7b02861
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic β-Azidation of Enones Initiated by an Electron-Donor–Acceptor Complex

Abstract: An operationally straightforward organocatalytic β-azidation of α,β-unsaturated ketones is described. Reaction of the Zhdankin azidoiodane with enones in the presence of a catalytic amount of an amine provides β-azido ketones via the formation of an electron-donor-acceptor complex. The application of this protocol is demonstrated through one-step elaborations leading to the synthesis of unprecedented classes of 1,2,3-triazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…(E)-3-Methyl-1-phenylhepta-1,6-dien-3-ol 1a was chosen as am odel substrate.T he alcohol 1a was first reacted with lithium hexamethyldisilazide (LiHMDS,1 .2 equiv) in 1.25 mL of 1,2-dimethoxyethane (DME) at room temperature for 0.5 h. After deprotonation, 1,4-diazabicyclo-[2.2.2]octane (DABCO,1 .5 equiv) [13] and perfluorobutyl iodide 2a (1.8 equiv) were added sequentially and the mixture was stirred under visible-light irradiation [using aP hilips Master HPI-T Plus (400 W) bulb] at 50 8 8Cfor 18 hours.T oour delight, the 1,4-alkenyl migration product 3a was obtained in 34 %yield with complete E selectivity ( -13). Replacing DABCO by other amines,s uch as N,N,N',N'-tetramethylethane-1,2-diamine (TMEDA), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU),a nd N,N,N',N'-tetramethyl-1,3-propanediamine (TMPDA), afforded lower yields ( Table 1, entries [14][15][16]. [14] Va rying the amount of base and DABCO showed that the highest yield (67 %) was obtained by using 1a (0.1 mmol), 2a (1.8 equiv), K 3 PO 4 (2.0 equiv), and DABCO (1.2 equiv With the optimized reaction conditions in hand, we investigated the scope of the reaction by keeping perfluorobutyl iodide 2a as the C-radical precursor and systematically varied the migrating styrenyl group (Table 2).…”
Section: Vicinalalkenedifunctionalizationisaverypowerfulstrategymentioning
confidence: 99%
See 2 more Smart Citations
“…(E)-3-Methyl-1-phenylhepta-1,6-dien-3-ol 1a was chosen as am odel substrate.T he alcohol 1a was first reacted with lithium hexamethyldisilazide (LiHMDS,1 .2 equiv) in 1.25 mL of 1,2-dimethoxyethane (DME) at room temperature for 0.5 h. After deprotonation, 1,4-diazabicyclo-[2.2.2]octane (DABCO,1 .5 equiv) [13] and perfluorobutyl iodide 2a (1.8 equiv) were added sequentially and the mixture was stirred under visible-light irradiation [using aP hilips Master HPI-T Plus (400 W) bulb] at 50 8 8Cfor 18 hours.T oour delight, the 1,4-alkenyl migration product 3a was obtained in 34 %yield with complete E selectivity ( -13). Replacing DABCO by other amines,s uch as N,N,N',N'-tetramethylethane-1,2-diamine (TMEDA), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU),a nd N,N,N',N'-tetramethyl-1,3-propanediamine (TMPDA), afforded lower yields ( Table 1, entries [14][15][16]. [14] Va rying the amount of base and DABCO showed that the highest yield (67 %) was obtained by using 1a (0.1 mmol), 2a (1.8 equiv), K 3 PO 4 (2.0 equiv), and DABCO (1.2 equiv With the optimized reaction conditions in hand, we investigated the scope of the reaction by keeping perfluorobutyl iodide 2a as the C-radical precursor and systematically varied the migrating styrenyl group (Table 2).…”
Section: Vicinalalkenedifunctionalizationisaverypowerfulstrategymentioning
confidence: 99%
“…Replacing DABCO by other amines,s uch as N,N,N',N'-tetramethylethane-1,2-diamine (TMEDA), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU),a nd N,N,N',N'-tetramethyl-1,3-propanediamine (TMPDA), afforded lower yields ( Table 1, entries [14][15][16]. [14] Va rying the amount of base and DABCO showed that the highest yield (67 %) was obtained by using 1a (0.1 mmol), 2a (1.8 equiv), K 3 PO 4 (2.0 equiv), and DABCO (1.2 equiv With the optimized reaction conditions in hand, we investigated the scope of the reaction by keeping perfluorobutyl iodide 2a as the C-radical precursor and systematically varied the migrating styrenyl group (Table 2). Electronic effects at the para position in the aryl moiety are not pronounced and the corresponding products 3b-3f were formed in moderate-to-good yields (Table 2, entries 1-5).…”
Section: Vicinalalkenedifunctionalizationisaverypowerfulstrategymentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal activation of these complexes is also possible. 17,18 Since only selected pairs of molecules form EDA complexes, there are only few reports in the literature for selective reactivity, even though these complexes have been known for decades. 12,19 In the vast majority of the examples, after electron transfer (ET) the electron donor (ED) radical cation and the electron acceptor (EA) radical anion react with each other to form the product (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…1416 Typically, this motif is synthesized by conjugate addition of an azide anion or by displacement of sensitive β -halo-ketones. 12,17,18…”
mentioning
confidence: 99%